"Life Is Movement, Movement Is Life!" Mobility Politics and the Circulatory State in Nazi Germany. Issue 5 (3rd December 2018) - Denning, Andrew
Abstract: Historians have long understood rootedness as a hallmark of the Nazi regime and German race thinking. Blood and Soil implied an intimate bond between lands and peoples, and the Nazis co-opted ideas of Heimat to claim that members of the German race were indelibly marked by their milieu. Meanwhile, German designs on living space and the creation of a land empire are hallmarks of the territorialized logic of "heavy" modernity. Closer attention to German engagements with mobility complicates this picture, however, demonstrating how the material effects, embodied experiences, and discursive renderings of movement in Nazi Germany influenced geopolitical calculations and everyday life in equal measure. The Nazis celebrated mobility as much as they cherished rootedness. Mobility politics lay at the foundation of power relations in the Third Reich, and the Nazis developed a set of institutions in the form of a circulatory state to manage the productive potential and disruptive danger of mobility. Systems and logics of mobility connected seemingly distinct realms of historical experience in Nazi Germany, suggesting the potential of mobility for historians who study other times and places.